Chlamydia trachomatis Serovars Drive Differential Production of Proinflammatory Cytokines and Chemokines Depending on the Type of Cell Infected - Faris, Robert; Andersen, Shelby E.; McCullough, Alix; Gourronc, Françoise; Klingelhutz, Aloysius J.; Weber, Mary M. (Frontiers in Cellular and Infection Microbiology, 2019)
Chlamydia trachomatis serovars A-C infect conjunctival epithelial cells and untreated infection can lead to blindness. D-K infect genital tract epithelial cells resulting in pelvic inflammatory disease, ectopic pregnancy, and sterility while L1-L3 infect epithelial cells and macrophages, causing an invasive infection. Despite some strains of Chlamydia sharing high nucleotide sequence similarity, the bacterial and host factors that govern tissue and cellular tropism remain largely unknown. Following introduction of C. trachomatis via intercourse, epithelial cells of the vagina, foreskin, and ectocervix are exposed to large numbers of the pathogen, yet their response to infection and the dynamics of chlamydial growth in these cells has not been well-characterized compared to growth in more permissive cell types that harbor C. trachomatis. We compared intracellular replication and inclusion development of representative C. trachomatis serovars in immortalized human conjunctival epithelial, urogenital epithelial, PMA stimulated THP-1 (macrophages), and HeLa cells. We demonstrate that urogenital epithelial cells of the vagina, ectocervix, and foreskin restrict replication of serovar A while promoting robust replication and inclusion development of serovar D and L2. Macrophages restrict serovars D and A while L2 proliferates in these cells. Furthermore, we show that GM-CSF, RANTES, GROα, IL-1α, IL-1β, IP-10, IL-8, and IL-18 are produced in a cell-type and serovar-specific manner. Collectively we have established a series of human cell lines that represent some of the first cell types to encounter C. trachomatis following exposure and show that differential production of key cytokines early during infection could regulate serovar-host cell specificity.